(untitled) (Enki & Ptah. Journal of Technology and Trade in Ancient Egypt and Western Asia, 2025)
Review of A. Bats and N. Licitra (eds), Storage in Ancient Egypt and Nubia. Earthen Architecture and Building Techniques, Sidestone Press, Leiden 2023, 196 p, 14 illus. (bw), 66 illus. (fc), Paperback ISBN: 9789464262230 - € 40,00, Hardback ISBN: 9789464262247- € 120,00, Free Enhanced Digital Edition